Comercialização de frutos de qualidade a importância dos tratamentos pós-colheita - Carvalho, José Márcio (1996)
The aim ofthis work was to perform a comparation between the production activities and fruit commercialization, showing that post-harvest treatments affect the commercial and productive structures directly. Five crops served as basis for the analysis: apple, banana, melon, grape and mango. These cultures were chosen because they produce the fruits most exported by Brazil, it means, are the fruits subjected most intensively to the postharvest processing. Variable costs ofproduction and commercialization were surveyed ofthe five crops above quoted. The commercialization costs were verified for two wholesale trading centers: São Paulo (standing for the homecommerce) and Rotterdam (standing for the foreign commerce). To the same five fruits, the successions ofpre-harvest, harvest and post-harvest were also assessed, this analysis contributed to a better understanding of the systemic structuration ofthe chain offruit production and commercialization. To the home market, it was found that the average cost of the commercialization ofapple, banana, melon, grape and mango accounted for 54.9% ofthe aggregated cost in these fruits up to the wholesaling levei, the rest (45.1%) of this cost, was encompassed by production activities. To the abroad commerce, the relative importance ofthe commercialization costs was still greater, these accounted for, on the average, 80.17% ofthe cost ofthe fruit commercialized abroad. It was upto the productive activities to encompass only 19.83% ofthe average value ofthe fruits sold in the abroad market. On the basis ofthe analysis ofproduction procedures and post-harvest processing ofapple, banana, melon, grape and mango, it was noticed that post-harvest directíy acted, imposing requirements or contributing with technical information, about the following steps: pre harvest, harvest, qualitative requirements for the fruits, offruit preparation, packing, storage and transportation. It follows that based on the analysis that the chain of fruit production and commercialization works as an open system, made up ofseveral interdependent subsystems which are joined together (coordinated) by post-harvest. One can say that postharvest bears the technological space which makes the existence of the fruit culture ofhigh standard feasible.